Coupling of the HPA and HPG Axes in the Context of Early Life Adversity in Incarcerated Male Adolescents - Dismukes, Andrew R. (Dev Psychobiol, 2014)
The effects of early life adversity can be observed across the lifespan, and the Hypothalamic-Pituitary-Adrenal (HPA) and Hypothalamic-Pituitary-Gonadal (HPG) axes could be mechanistic intermediaries underlying this phenomenon. The current study examined fifty adolescent males aged 12–18 in a maximum-security correctional and treatment setting. Saliva samples were collected five times a day for two day and assayed for cortisol, testosterone and DHEA. Youth completed semi-structured life stress interviews and self-reports of child maltreatment to index adversity. When youth had higher testosterone levels, they had higher cortisol and DHEA levels, indicating positive “coupling” of the HPA- HPG axes. In addition, children experiencing greater life adversity had tighter coupling of the HPA-HPG axes. Additional analyses hint that coupling may be driven largely by HPG axis functioning. Results indicate that positive coupling of the HPA-HPG axis is observed within incarcerated adolescents, especially for those with the greatest life stress.